Functionalization of Oxazolo[4, 5‐b]pyrazines by Deprotometallation. Issue 29 (10th July 2018) - Bisballe, Niels; Hedidi, Madani; Demmer, Charles S.; Chevallier, Floris; Roisnel, Thierry; Dorcet, Vincent; Halauko, Yury S.; Ivashkevich, Oleg A.; Matulis, Vadim E.; Bentabed‐Ababsa, Ghenia; Bunch, Lennart; Mongin, Florence
Abstract : Different 2‐arylated oxazolo[4, 5‐ b ]pyrazines, obtained by palladium(II)‐catalyzed domino reaction from 2, 3‐dichloropyrazine and the corresponding carboxamides, were functionalized by deprotometallation. Employing lithium 2, 2, 6, 6‐tetramethylpiperidine, in order to form a lithio derivative, and then trapping it by iodolysis, proved to be inefficient. However, the presence of a zinc‐based in situ trap allowed most substrates to be functionalized. Deprotonation of the pyrazine ring was observed in the presence of tolyl and anisyl groups at the oxazole 2‐position. In contrast, with chlorophenyl and thienyl groups in this 2‐position, deprotonation rather occurred on these groups either competitively or exclusively. The regioselectivities were discussed in the light of calculated p K a values of the substrates in THF. Finally, in the case of 2‐phenyloxazolo[4, 5‐ b ]pyrazine, we converted the mixture of 5‐ and 6‐iodinated products into the corresponding 5, 6‐diiodide, which was further functionalized by a double Suzuki coupling. Abstract : Functionalizations of 2‐arylated oxazolo[4, 5‐ b ]pyrazines are reported. Access to the corresponding iodides was investigated, and deprotolithiation in the presence of a zinc‐based in situ trap proved to be the most efficient approach. Triarylated oxazolo[4, 5‐ b ]pyrazines were synthesized from a diiodo derivative obtained by iterative deprotonation‐iodolysis.